Moral Objectivism in Cross-Cultural Perspective - Beebe, James (Journal of cognition and culture, 2015)
Moral psychologists have recently turned their attention to the study of folk metaethical beliefs. We report the results of a cross-cultural study using Chinese, Polish and Ecuadorian participants that seeks to advance this line of investigation. Individuals in all three demographic groups were observed to attribute objectivity to ethical statements in very similar patterns. Differences in participants’ strength of opinion about an issue, the level of societal agreement or disagreement about an issue, and participants’ age were found to significantly affect their inclination to view the truth of an ethical statement as a matter of objective fact. Implications for theorizing about folk morality are discussed.